Method for producing catalyst for producing vinyl acetate, and method for producing vinyl acetate

In the production of vinyl acetate catalyst, the problem of uneven aggregation and hydrolysis rate of gold particles is solved by reacting compounds of copper, palladium and gold with alkali and undergoing pH-controlled reduction treatment, and the selection rate and activity of the catalyst are improved.

CN119136910APending Publication Date: 2024-12-13CRASUS CHEMICAL INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037749.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-08-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The aggregation of gold particles in the existing vinyl acetate production catalysts leads to a decrease in catalytic activity, affecting the selection rate of vinyl acetate, and the uneven hydrolysis rate leads to the inconsistency of gold and palladium, affecting the catalytic performance.

Method used

During the catalyst manufacturing process, the compound containing copper, palladium and gold is first reacted with the alkali component and put into the support excess, and then separated and reduced in water with pH 7.0 to 11.5 to ensure a reasonable state of gold and palladium. and the high activity of the catalyst.

Benefits of technology

The selection rate of vinyl acetate and the performance of the catalyst are significantly improved, the aggregation of gold particles is avoided, and high catalytic activity is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112384960000141
    Figure BDA0005112384960000141
Patent Text Reader

Abstract

A production method for producing a catalyst for vinyl acetate production, the catalyst comprising a carrier, copper, palladium, gold, and an acetate, the production method comprising the following steps in this order: step 1. A step for impregnating the carrier with an alkali solution; a step (2) for bringing the carrier into contact with and impregnating the carrier with a solution containing a copper-containing compound, a palladium-containing compound, and a gold-containing compound in excess amounts with respect to the desired loading amounts of the catalyst components; a step (3) for separating the carrier from the solution when the desired supporting amount of each catalyst component is supported by the carrier; a step 4 of bringing the carrier into contact with water or an aqueous solution having a pH of 7.0-11.5; step 5, performing a reduction treatment; and step 6, a step for supporting the acetate on the carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing a vinyl acetate production catalyst used when producing vinyl acetate using acetic acid, ethylene, and oxygen as raw materials, and a method for producing vinyl acetate using the catalyst. Background Art

[0002] Vinyl acetate is an important industrial material used in a wide range of fields such as coatings, adhesives, and fiber treatment agents as a raw material for vinyl acetate resins, a raw material for polyvinyl alcohol, and a copolymer monomer with ethylene, styrene, acrylates, methacrylates, etc.

[0003] As a catalyst for the production of vinyl acetate using acetic acid, ethylene and oxygen as raw materials, a catalyst obtained by supporting palladium, gold and potassium acetate on silica is widely used. The active site in the reaction is believed to be palladium, and gold is believed to have the effect of reducing the generation of carbon dioxide as a byproduct, thereby improving the selectivity of vinyl acetate, in addition to inhibiting the aggregation of palladium. In order to exert the effect of gold, it is necessary for gold atoms to exist close to palladium. In Patent Document 1, by improving the impregnation process into the carrier, these metals are supported in a state where the supporting sites of palladium and gold are close to each other.

[0004] In the production of vinyl acetate, improving the selectivity of vinyl acetate is an important technical issue, and suppressing the generation of carbon dioxide is also desired from the viewpoint of environmental load.

[0005] In Patent Document 2, the selectivity of vinyl acetate is improved by supporting copper in addition to palladium and gold.

[0006] Patent Document 3 discloses a method for producing a catalyst containing palladium, gold, and copper, wherein a compound containing palladium, a compound containing gold, and a compound containing copper are supported on a carrier through the same step, thereby improving the selectivity of vinyl acetate.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-080326

[0010] Patent Document 2: Japanese Patent Application No. 2002-516749

[0011] Patent Document 3: International Publication No. 2022 / 113429 Summary of the invention

[0012] Problems to be solved by the invention

[0013] In patent document 3, an alkali component is loaded on a carrier, and then a solution containing a compound containing palladium, a compound containing gold, and a compound containing copper is impregnated in the carrier through the same process, and each compound is hydrolyzed, thereby making the hydroxide of palladium, the hydroxide of gold, and the hydroxide of copper loaded on the carrier. The compound containing gold represented by chloroauric acid is usually hydrolyzed slowly, and the speed of being loaded by the carrier is slow. Therefore, even if the compound containing palladium and the compound containing gold are contacted with the carrier loaded with an alkali component through the same process, due to the difference in the hydrolysis rate of palladium and gold, gold atoms that are not close to palladium will be generated, or the compound containing gold retained in the solution will agglomerate and coarsen to generate agglomerates of gold particles. However, if a compound containing copper coexists during the hydrolysis of the compound containing gold, the compound containing copper is rapidly hydrolyzed and loaded on the carrier, and then the compound containing gold is adsorbed to the hydrolyzate of the compound containing copper loaded on the carrier, thereby increasing the hydrolysis rate of the compound containing gold. Therefore, compared with the case where the copper-containing compound is not added in the same step, gold can be supported in a state close to palladium, and the coarsening of gold particles in the solution can be suppressed, and as a result, the selectivity of vinyl acetate can be improved. However, aggregation of gold particles is also observed in the catalyst produced by this production method, and therefore, if gold aggregation in the hydrolysis step and the reduction step of catalyst production can be further improved, the performance of the catalyst can be expected to be further improved.

[0014] The present disclosure provides a method for producing a catalyst, which can produce vinyl acetate with improved selectivity while ensuring high catalytic activity.

[0015] Means for solving problems

[0016] The inventors of the present application have repeatedly conducted intensive studies to solve the above-mentioned problems and have discovered a method for producing a catalyst, characterized in that when compounds respectively containing copper, palladium and gold are reacted with an alkali component while being supported on a carrier, the compounds respectively containing each metal are added in excess compared to the amount of the compounds respectively containing each metal corresponding to the desired supported amount of each metal, and a solution of the compounds respectively containing each metal is separated from the carrier at a time point when the metal supported amount reaches a desired value, and then the carrier is contacted with water or an aqueous solution with a pH of 7.0 to 11.5, followed by a reduction treatment, thereby successfully producing vinyl acetate with an improved selectivity.

[0017] That is, the contents of the present disclosure include the following [1] to

[13] . [1]

[0019] A method for producing a catalyst for producing vinyl acetate, comprising a carrier, copper, palladium, gold and acetate, the method comprising the following steps in sequence:

[0020] Step 1. A step of impregnating the carrier with an alkaline solution;

[0021] Step 2. A step of contacting and impregnating the support with a solution containing copper, palladium and gold as catalyst components and containing a compound containing copper, a compound containing palladium and a compound containing gold in excess amounts relative to a desired amount of each catalyst component supported;

[0022] Step 3. When the desired amount of each catalyst component is supported by the carrier, a step of separating the carrier from the solution;

[0023] Step 4. a step of contacting the carrier with water or an aqueous solution having a pH of 7.0 to 11.5;

[0024] Step 5. A step of performing a reduction treatment; and

[0025] Step 6. A step of causing the carrier to support acetate. [2]

[0027] The production method according to [1], wherein the aqueous solution used in the step 4 is an aqueous solution having a pH of 8.0 to 11.0. [3]

[0029] The production method according to [2], wherein the aqueous solution having a pH of 8.0 to 11.0 is a pH buffer solution. [4]

[0031] According to the production method described in [3], the pH buffer solution is any buffer solution selected from the group consisting of a carbonate-bicarbonate buffer solution, a sodium borate buffer solution, and a potassium borate buffer solution. [5]

[0033] According to the production method described in [3], the pH buffer solution is a carbonic acid-bicarbonic acid buffer solution. [6]

[0035] The production method according to any one of [1] to [5], wherein in the step 2, the excess rate of the input amount of the gold-containing compound relative to the desired gold loading amount is 2% to 150%. [7]

[0037] The production method according to any one of [1] to [6], wherein in the step 2, the excess rate of the input amount of the palladium-containing compound relative to the desired palladium loading amount is 2% to 50%. [8]

[0039] The production method according to any one of [1] to [7], wherein in the step 2, the excess rate of the input amount of the copper-containing compound relative to the desired copper loading amount is 2% to 50%. [9]

[0041] The production method according to any one of [1] to [8], wherein the mass of the metallic copper supported per 1 kg of the carrier is 0.25 g to 5.00 g.

[10]

[0043] The production method according to any one of [1] to [9], wherein the mass of the metal palladium supported on 1 kg of the carrier is 5.00 g to 20.0 g.

[11]

[0045] The production method according to any one of [1] to

[10] , wherein the mass of the metallic gold supported per 1 kg of the carrier is 4.00 g to 20.0 g.

[12]

[0047] The production method according to any one of [1] to

[11] , wherein the mass of the acetate supported on 1 kg of the carrier is 40 g to 125 g.

[13]

[0049] A method for producing vinyl acetate, using the catalyst for producing vinyl acetate obtained by the method described in any one of [1] to

[12] as a catalyst, and using ethylene, oxygen and acetic acid as raw materials.

[0050] Effects of the Invention

[0051] AuCl is formed by reacting a compound containing gold, such as chloroauric acid, with an alkali component. 3-n (OH) n and Au(OH)3. If Cl - When the gold is coordinated and reduced, the gold particle size increases and the gold particles aggregate. The higher the pH in the solution, the more it promotes the reduction from Cl - On the other hand, if the pH of the solution becomes too high, gold will be replaced by [Au(OH)4] - redissolved in the form of

[0052] According to the method disclosed in the present invention, the pH of the solution after the reaction with the alkali component is controlled to a level that allows the gold to be in a state close to Cl-free. - The coordination state is Au(OH)3, and the aggregation of gold particles in the reduction process can be suppressed within a range where gold does not dissolve again, thereby producing a catalyst for the production of vinyl acetate having an alloy state of palladium and gold suitable for the production reaction of vinyl acetate. As a result, compared with the conventional method, it is possible to significantly improve the selectivity of vinyl acetate while ensuring high catalytic activity. DETAILED DESCRIPTION

[0053] Embodiments of the present invention will be described below, but the present invention is not limited to these embodiments, and various modifications can be made within the scope of the present invention.

[0054] In this specification, when "to" is used for a numerical range, the numerical values ​​at both ends are the upper limit and the lower limit, respectively, and are included in the numerical range.

[0055] [Method for producing a catalyst for producing vinyl acetate]

[0056] A method for producing a catalyst for producing vinyl acetate according to one embodiment includes the following steps in order. It should be noted that copper, palladium, and gold are sometimes referred to as "catalyst components", and compounds containing copper, compounds containing palladium, and compounds containing gold are collectively or separately referred to as "raw material compounds" for each metal.

[0057] Step 1. Step of impregnating the carrier with an alkaline solution

[0058] Step 2. A step of contacting and impregnating the support with a solution (hereinafter also referred to as "solution A") containing copper, palladium and gold as catalyst components and containing a compound containing copper, a compound containing palladium and a compound containing gold in excess amounts relative to the desired amount of each catalyst component supported.

[0059] Step 3. When the desired catalyst component loading amount is supported on the carrier, a step of separating the carrier from the solution A

[0060] Step 4. Step of contacting the carrier with water or an aqueous solution having a pH of 7.0 to 11.5

[0061] Step 5. Reduction treatment step

[0062] Step 6. Step of making the carrier carry acetate

[0063] In one embodiment, step 2 is performed after step 1 to contact and impregnate a support with solution A containing a compound containing copper, a compound containing palladium, and a compound containing gold to form a catalyst precursor in which a reaction product of these compounds and a basic compound is supported on the support.

[0064] Steps 1 to 6 are performed in the above order, but other steps may be included for the purpose of improving the performance of the catalyst. For example, a step of washing the carrier with water after step 5 may be mentioned. The reduction treatment in step 5 is a treatment for converting the reactants of the raw material compound and the alkaline compound into metallic copper, metallic palladium and metallic gold, respectively, and therefore must be performed after step 4. It should be noted that, as an exception, step 5 and step 6 may be replaced. Each step is described in detail below.

[0065] <Step 1. Step of impregnating the support with an alkaline solution>

[0066] In this step, the carrier is impregnated with an alkali solution. This step can be performed at room temperature. After the impregnation operation is completed, the carrier can be dried, or the next step can be performed without drying or the like.

[0067] As a carrier, there is no particular limitation, and a porous substance commonly used as a catalyst carrier can be used. The carrier is preferably silica, alumina, silica-alumina, diatomaceous earth, montmorillonite or titanium dioxide, and more preferably silica. In the case of using a substance with silica as the main component as a carrier, the silica content of the carrier is usually at least 50% by mass, preferably at least 90% by mass, relative to the mass of the carrier.

[0068] The specific surface area of ​​the support measured by the BET method is preferably at least 0.01 m 2 / g, more preferably 10 to 1000 m 2 The range of m / g is particularly preferably 100 to 500 m 2 / g range. The volume density of the carrier is preferably in the range of 50 to 1000 g / L, and particularly preferably in the range of 400 to 500 g / L. The water absorption rate of the carrier is preferably in the range of 0.05 to 3 g-water / g-carrier, and particularly preferably in the range of 0.1 to 2 g-water / g-carrier. For the pore structure of the carrier, the average pore diameter is preferably in the range of 1 to 1000 nm, and particularly preferably in the range of 2 to 800 nm. If the average pore diameter is greater than 1 nm, the diffusion of the gas can be facilitated. On the other hand, if the average pore diameter is less than 1000 nm, the specific surface area of ​​the carrier required to obtain catalytic activity can be ensured.

[0069] In the determination of the pore diameter distribution of the carrier, the mercury intrusion method and the gas adsorption method (BJH method) are widely used. According to the classification of pores by IUPAC (International Union of Pure and Applied Chemistry), large pores of 50 nm or more and a part of medium pores of 2 nm or more and less than 50 nm can be measured by the mercury intrusion method, and medium pores and micropores of 2 nm or less can be measured by the gas adsorption method. The appropriate measurement method can be selected according to the size of the pore diameter.

[0070] In the present disclosure, the water absorption rate of a carrier refers to a value measured by the following measurement method.

[0071] 1. Use a balance to measure about 5 g of the carrier (W1 g) and put it into a 100 mL beaker.

[0072] 2. Add about 15 mL of pure water (ion-exchanged water) into the beaker in such a way as to completely cover the carrier.

[0073] 3. Leave it for 30 minutes.

[0074] 4. Pour the contents of the beaker onto a metal mesh and drain the pure water.

[0075] 5. Remove the water adhering to the surface of the carrier by gently pressing with a paper towel until the gloss on the surface disappears.

[0076] 6. Measure the total mass of the carrier and pure water (W2g).

[0077] 7. Calculate the water absorption rate of the carrier by the following formula.

[0078] Water absorption (g-water / g-carrier) = (W2-W1) / W1

[0079] Therefore, the amount of water absorbed by the carrier (g) is calculated by the water absorption rate of the carrier (g-water / g-carrier)×the mass of the carrier used (g).

[0080] The shape of the carrier is not particularly limited. Specific examples include powder, spherical and pelletized forms, but are not limited thereto. The most suitable shape can be selected in accordance with the reaction form, reactor, etc. adopted.

[0081] The size of the carrier particles is not particularly limited. When the carrier is spherical, the particle diameter is preferably in the range of 1 to 10 mm, more preferably in the range of 3 to 8 mm. In the case of filling a tubular reactor with a catalyst for a gas phase reaction, if the particle diameter is 1 mm or more, it is possible to prevent excessive increase in pressure loss when the gas is circulated, and to effectively circulate the gas. On the other hand, if the particle diameter is 10 mm or less, it is easy to diffuse the raw gas into the catalyst, and the catalytic reaction can be effectively carried out. In addition, the number of catalyst particles filled into the tubular reactor will not be excessively reduced, and therefore, it is possible to ensure that the total surface area of ​​the catalyst particles is sufficient to make the metal components (copper, palladium, gold, etc.) dispersed on the surface of the carrier suitable for the reaction.

[0082] The alkaline solution may be a solution of any alkaline compound. Examples of the alkaline compound include hydroxides of alkali metals or alkaline earth metals, bicarbonates of alkali metals or alkaline earth metals, carbonates of alkali metals or alkaline earth metals, and silicates of alkali metals or alkaline earth metals. As the alkali metal, lithium, sodium or potassium may be used. As the alkaline earth metal, barium or strontium may be used. As the alkaline compound, sodium metasilicate, potassium metasilicate, sodium hydroxide, potassium hydroxide, barium hydroxide or strontium hydroxide may be suitably used.

[0083] The solvent of the alkaline solution is not particularly limited, and examples thereof include water, methanol, and ethanol, and water is preferred.

[0084] The basic compound is used in excess of the total amount of the desired supported amount of copper, palladium and gold described later. For example, the product of the molar amount of the basic compound and the valence of the basic compound is preferably greater than 1.1 times and less than 3.0 times the sum of the product of the molar amount of the compound containing palladium and the valence of palladium, the product of the molar amount of the compound containing gold and the valence of gold, and the product of the molar amount of the compound containing copper and the valence of copper, more preferably greater than 1.5 times and less than 2.0 times.

[0085] There is no particular limitation on the method of impregnating the carrier with the alkaline solution. For example, method (I) includes briefly immersing the carrier in a large amount of alkaline solution and then taking out the carrier impregnated with the alkaline solution in an amount corresponding to the amount of water absorbed; and method (II) includes dissolving an alkaline compound in a solvent, fixing the volume to a value corresponding to the amount of water absorbed by the carrier, and impregnating the carrier with the resulting solution. From the perspective of waste liquid treatment, method (II) is preferred.

[0086] The alkaline solution is preferably impregnated into the carrier in an amount equivalent to 0.9 to 1.0 times by mass of the water absorption of the carrier, and more preferably impregnated into the carrier in an amount equivalent to 0.95 to 1.0 times by mass of the water absorption of the carrier. If the amount of the alkaline solution is more than 0.9 times by mass of the water absorption of the carrier, uneven impregnation of the alkaline solution is not easy to occur. If the amount of the alkaline solution is less than 1.0 times by mass of the water absorption of the carrier, the carrier can reliably absorb the entire amount of the alkaline solution. In the present disclosure, the water absorption of the carrier is a value measured using pure water, which is strictly different from the value for the alkaline solution, but is used directly for convenience.

[0087] <Step 2. Step of contacting and impregnating the support with solution A>

[0088] In this step, the carrier impregnated with the alkaline solution is contacted and impregnated with solution A. Solution A is a solution containing a compound containing copper, a compound containing palladium, and a compound containing gold. Solution A may contain other components as needed.

[0089] In solution A, the desired catalyst composition, that is, the excess amount of each raw material compound (compounds containing copper, compounds containing palladium, and compounds containing gold) obtained by inverse calculation of each loading amount of the catalyst components (metallic copper, metal palladium, and metal gold) in the final catalyst is put in advance. That is, the raw material compound of the amount obtained by multiplying the amount of the raw material compound equivalent to the desired catalyst component loading amount by each excess rate is dissolved in such a way that the compound containing copper, the compound containing palladium, and the compound containing gold are all in excess compared to the desired catalyst component loading amount. The concentration of the raw material compound of the catalyst components (copper, palladium, and gold) in solution A can be calculated based on the amount of the raw material compound and the amount of solution calculated as described above. In actual operation, the necessary amount (g) of the raw material compound is measured and dissolved in the solvent in a manner that becomes the preferred solution amount.

[0090] The excess ratio of the input amount of the raw material compound of each catalyst component in the solution A was calculated by the following formula.

[0091] (Amount (mass) of catalyst component in the raw material compound - Amount (mass) of desired catalyst component to be supported) / (Amount (mass) of desired catalyst component to be supported) × 100 (%)

[0092] When the catalyst component is gold, the amount (g) of the compound containing gold (e.g., chloroauric acid) corresponding to the amount (g) to be carried per 1 kg of the carrier is calculated, multiplied by the amount of the carrier (kg) and (excess rate of the compound containing gold + 100) / 100, and the obtained amount (g) of the compound containing gold is dissolved in the solvent of solution A. Specifically, if the amount (g) of gold to be carried per 1 kg of the carrier is set to 10 g, the amount of chloroauric acid (HAuCl4) containing 10 g of gold atoms is 17.26 g. When the excess rate is set to 80%, the input amount of chloroauric acid per 1 kg of the carrier is 31.068 g (=17.26×((80+100) / 100). This value is multiplied by the amount of the carrier used (kg) and the obtained amount of chloroauric acid is dissolved in the solvent of solution A. Solution A is prepared in the same manner for palladium and copper.

[0093] The excess rate of the input amount of the compound containing gold in solution A is preferably 2% or more, more preferably 20% or more, and further preferably 75% or more. The excess rate of the input amount of the compound containing gold in solution A is preferably 150% or less, more preferably 100% or less, and further preferably 90% or less. These upper and lower limits can be combined arbitrarily. The excess rate of the input amount of the compound containing gold in solution A is preferably 2% to 150%, more preferably 20% to 100%, and further preferably 75% to 90%. The excess rate of the input amount of the compound containing palladium in solution A is preferably 2% or more, more preferably 5% or more, and further preferably 10% or more. The excess rate of the input amount of the compound containing palladium in solution A is preferably 50% or less, more preferably 40% or less, and further preferably 20% or less. These upper and lower limits can be combined arbitrarily. The excess rate of the input amount of the compound containing palladium in solution A is preferably 2% to 50%, more preferably 5% to 40%, and further preferably 10% to 20%. The excess rate of the input amount of the copper-containing compound in solution A is preferably 2% or more, more preferably 5% or more, and further preferably 8% or more. The excess rate of the input amount of the copper-containing compound in solution A is preferably 50% or less, more preferably 40% or less, and further preferably 15% or less. These upper and lower limits may be combined arbitrarily. The excess rate of the input amount of the copper-containing compound in solution A is preferably 2% to 50%, more preferably 5% to 40%, and further preferably 8% to 15%.

[0094] By using a solution A containing an excess amount of the raw material compound relative to the desired catalyst component loading, the contact time between the support and solution A required to obtain the desired catalyst component loading can be shortened. This can suppress the coarsening of gold particles caused by the dissolution and reprecipitation process.

[0095] A copper precursor that can be converted into metallic copper can be used as the compound containing copper in solution A. Examples of the copper precursor that can be converted into metallic copper include copper chloride, copper acetate, and copper nitrate, and copper chloride is preferably used.

[0096] A palladium precursor that can be converted into metallic palladium can be used as the compound containing palladium in solution A. Examples of the palladium precursor that can be converted into metallic palladium include palladium chloride, palladium nitrate, palladium sulfate, sodium chloropalladate, potassium chloropalladate, barium chloropalladate, and palladium acetate, and sodium chloropalladate is preferably used.

[0097] A gold precursor that can be converted into metallic gold can be used as the compound containing gold in solution A. Examples of the gold precursor include chloroauric acid, sodium chloroaurate, and potassium chloroaurate, and chloroauric acid is preferably used.

[0098] Examples of the solvent of solution A include water, alcohols, and organic acids. Water is preferred because it does not damage the carrier and has no reactivity with the compound contained in solution A.

[0099] The amount of solution A is preferably 1.0 to 10.0 times by mass, more preferably 2.0 to 8.0 times by mass, and particularly preferably 2.0 to 5.0 times by mass the amount of water absorbed by the carrier.

[0100] By contacting and impregnating the support impregnated with the alkaline solution with the solution A, the raw material metal compound can be converted into a water-insoluble substance, thereby forming a shell-type catalyst precursor in which metal components such as palladium, gold and copper are supported so as to be localized on the surface of the support.

[0101] The contact temperature is not particularly limited, but is preferably 10 to 80° C., more preferably 20 to 60° C. When the contact temperature is 10° C. or higher, the conversion reaction can be sufficiently advanced. When the contact temperature is 80° C. or lower, the aggregation of gold, palladium, and copper can be suppressed.

[0102] For the contact time, the pre-experiment is repeatedly performed in advance to confirm the time change of the loading rate of the catalyst component at the specified contact temperature, and is set to the time to reach the desired loading amount. The contact time cannot be changed according to each catalyst component, so the excess rate of the input amount of each raw material compound is adjusted in advance in a manner to become the desired loading amount within the contact time. The contact time is preferably 0.5 to 100 hours, more preferably 1 to 20 hours. By making the contact time less than 100 hours, the degradation of the carrier can be suppressed.

[0103] <Step 3. Step of separating the carrier from the solution>

[0104] In this process, only the carrier is taken out from the mixture of the carrier and the solution obtained in process 2. The hydrolysis rate of compounds containing gold such as chloroauric acid is significantly lower than that of compounds containing palladium and compounds containing copper. Therefore, if the carrier is immersed in solution A for a long time, it is easy to produce compositional inhomogeneity in the carrier. In addition, if the carrier is immersed in solution A for a long time, the coarsening of gold particles is easy to occur during the dissolution and reprecipitation process. In contrast, when the desired amount of catalyst components is supported by the carrier, the carrier is separated from solution A, thereby suppressing the generation of compositional inhomogeneity and the coarsening of gold particles. There is no particular restriction on the separation method of the carrier and the solution, and it can be appropriately determined according to conventional methods in consideration of the shape and form of the catalyst. For example, filtration, centrifugal separation, sedimentation, etc. can be used, preferably filtration. As a method of filtering, a method of passing through a sieve smaller than the size of the carrier can be cited. When the carrier size is 3 to 8 mm, for example, it can be passed through a sieve with a mesh size of 2 mm. The solution is preferably separated by solid-liquid separation to a value that is 1.2 times or less of the water absorption rate of the carrier.

[0105] <Step 4. Step of contacting the carrier with water or an aqueous solution having a pH of 7.0 to 11.5 (hereinafter also referred to as "solution B")>

[0106] In this step, solution B is brought into contact with the support separated from the solution after being impregnated with solution A. Although it is an inference, the operation of step 4 can make the state of gold close to Cl-free. - The coordinated Au(OH) 3 can be expected to have the effect of suppressing the aggregation of gold in the next step 5 (reduction step). Solution B may be stirred slowly, but is preferably left to stand in order to prevent damage to the support.

[0107] Solution B is water or an aqueous solution having a pH of 7.0 to 11.5 at the temperature of step 4 (for example, room temperature (20°C)). The above pH is the pH of solution B before contact with the carrier. The above pH is above 7.0, preferably above 8.0. The above pH is below 11.5, preferably below 11.0. These upper and lower limits can be combined arbitrarily. The above pH is preferably 8.0 to 11.0. In step 4, the pH may also deviate from the above range, but it is preferred to maintain the pH within the above range. In the present disclosure, the pH is a value measured using a pH meter (for example, a desktop pH meter, manufactured by HORIBA ADBAND TECHNO Co., Ltd.) at the temperature of step 4. Solution B may be water alone or an alkaline aqueous solution. Other components may be dissolved in solution B as needed.

[0108] In the case where solution B is an alkaline aqueous solution, the solution can be an aqueous solution of any alkaline compound. As the alkaline compound, for example, hydroxides of alkali metals or alkaline earth metals, bicarbonates of alkali metals or alkaline earth metals, carbonates of alkali metals or alkaline earth metals, and silicates of alkali metals or alkaline earth metals can be mentioned. As the alkali metal, lithium, sodium or potassium can be used. As the alkaline earth metal, barium or strontium can be used. As the alkaline compound, sodium metasilicate, potassium metasilicate, sodium hydroxide, potassium hydroxide, barium hydroxide or strontium hydroxide can be suitably used.

[0109] As solution B, a pH buffer solution is preferably used to reduce the pH change in step 4. The pH of the pH buffer solution before contacting the support is preferably 7.0 to 11.5, more preferably 8.0 to 11.0. By using a pH buffer solution, the pH of solution B can be prevented from becoming excessively high and causing redissolution of gold. Examples of the pH buffer solution include phosphate (sodium) buffer solutions (pH 5.8 to 7.8), citrate (sodium) buffer solutions (pH 6.0 to 8.0), phosphate-buffered saline solutions (pH 6.4 to 8.4), ethylenediaminetetraacetic acid (sodium) buffer solutions (pH 7.0 to 9.0), Tris-hydrochloric acid buffer solutions (pH 7.0 to 9.0), Tris-EDTA buffer solutions (pH 7.0 to 9.0), acetic acid-ethanolamine buffer solutions (pH 8.6 to 10.6), boric acid (potassium) buffer solutions (pH 8.1 to 10.1), boric acid (sodium) buffer solutions (pH 8.1 to 10.1), and carbonic acid-bicarbonic acid buffer solutions (pH 9.0 to 11.0). Preferably, a boric acid (potassium) buffer solution, a boric acid (sodium) buffer solution, or a carbonic acid-bicarbonic acid buffer solution is used, and more preferably, a carbonic acid-bicarbonic acid buffer solution is used. In addition, regarding each buffer solution, (sodium) means that the counter ion is sodium, and (potassium) means that the counter ion is potassium.

[0110] The amount of solution B is preferably 1.0 to 10.0 times by mass, more preferably 2.0 to 8.0 times by mass, and particularly preferably 2.0 to 5.0 times by mass the amount of water absorbed by the carrier.

[0111] The temperature of solution B in step 4 is not particularly limited, but is preferably 10 to 80° C., more preferably 20 to 60° C. When the contact temperature is 10° C. or higher, the conversion reaction can be sufficiently advanced. When the contact temperature is 80° C. or lower, the aggregation of gold, palladium, and copper can be suppressed.

[0112] The contact time with solution B is preferably 0.1 hour to 48 hours, more preferably 1.0 hour to 24 hours.

[0113] <Step 5. Step of performing reduction treatment>

[0114] It is desirable to subject the carrier carrying the reactant of the raw material compound and the alkaline compound to a reduction treatment so that the reactant becomes metallic palladium, metallic gold and metallic copper. In the present disclosure, the so-called "metallic copper", "metallic palladium" and "metallic gold" refer to metal species having a valence of 0. The reduction treatment may be performed by either liquid phase reduction or gas phase reduction. It is also possible to reduce all palladium, gold and copper to a metallic state, i.e., 0 valence, without the reduction treatment.

[0115] Liquid phase reduction can be performed using any of non-aqueous or aqueous systems using alcohols or hydrocarbons. As a reducing agent, for example, carboxylic acids and salts thereof, aldehydes, hydrogen peroxide, sugars, polyphenols, boron compounds, amines or hydrazine can be used. As carboxylic acids and salts thereof, for example, oxalic acid, potassium oxalate, formic acid, potassium formate, potassium citrate and ammonium citrate can be mentioned. As aldehydes, for example, formaldehyde and acetaldehyde can be mentioned. As sugars, for example, glucose can be mentioned. As polyphenols, for example, hydroquinone can be mentioned. As boron compounds, for example, diborane and sodium borohydride can be mentioned. As a reducing agent, hydrazine, formaldehyde, acetaldehyde, hydroquinone, sodium borohydride and potassium citrate are preferred, and hydrazine is particularly preferred.

[0116] When liquid phase reduction is performed, there is no particular restriction on the temperature, but the liquid phase temperature is preferably set in the range of -10 to 100°C, more preferably in the range of 0 to 50°C. If the liquid phase temperature is above -10°C, a sufficient reduction rate can be obtained. On the other hand, if the liquid phase temperature is below 100°C, the agglomeration of copper, palladium and gold can be suppressed. There is no particular restriction on the reduction time, but the reduction time is preferably in the range of 0.5 to 24 hours, more preferably in the range of 1 to 10 hours. If the reduction time is more than 0.5 hours, the reduction can be fully carried out. On the other hand, if the reduction time is less than 24 hours, the agglomeration of copper, palladium and gold can be suppressed.

[0117] The reducing agent used in the gas phase reduction can be selected from, for example, hydrogen, carbon monoxide, alcohol, aldehyde, and olefins such as ethylene, propylene, and isobutylene. The reducing agent is preferably hydrogen. In the gas phase reduction, an inert gas can be added as a diluent. Examples of the inert gas include helium, argon, and nitrogen.

[0118] In the case of gas phase reduction, there is no particular restriction on the temperature, but it is preferred to heat the impregnated carrier to a range of 30 to 350°C, more preferably to a range of 100 to 300°C. If the heating temperature is above 30°C, a sufficient reduction rate can be obtained. On the other hand, if the heating temperature is below 300°C, the agglomeration of copper, palladium and gold can be suppressed. There is no particular restriction on the reduction time, but the reduction time is preferably in the range of 0.5 to 24 hours, more preferably in the range of 1.0 to 10 hours. If the reduction time is more than 0.5 hours, the reduction can be fully carried out. On the other hand, if the reduction time is less than 24 hours, the agglomeration of copper, palladium and gold can be suppressed.

[0119] The pressure of the gas phase reduction is not particularly limited, but is preferably in the range of 0.0 to 3.0 MPaG (gauge pressure), and more preferably in the range of 0.1 to 1.0 MPaG (gauge pressure) from the viewpoint of equipment.

[0120] When performing gas phase reduction, the supply rate of the reducing agent is preferably 10 to 15000 hr at a space velocity (hereinafter referred to as SV) under standard conditions. -1 The range of 100 to 8000 hr is particularly preferred. -1 range.

[0121] The reduced carrier is washed with pure water or the like as required. Washing can be performed continuously or in batches. The washing temperature is preferably in the range of 5 to 200° C., more preferably in the range of 15 to 80° C. There is no particular restriction on the washing time, and sufficient conditions can be selected for the purpose of removing the remaining undesirable impurities. Examples of undesirable impurities include chlorine-containing compounds and chloride ions. After washing, the carrier can be heated and dried as required.

[0122] <Step 6. Step of causing a carrier to support acetate>

[0123] Acetate can be loaded by, for example, impregnating a support with a solution containing a necessary amount of acetate and drying. The amount of acetate solution used is preferably 0.9 to 1.0 times by mass of the amount of water absorbed by the support. Typically, loading of acetate is performed after reduction treatment, but may also be performed before reduction treatment.

[0124] The acetate is preferably at least one compound selected from alkali metal acetates and alkaline earth metal acetates, and is more preferably an alkali metal acetate. Examples of the alkali metal acetate include acetates of lithium, sodium, and potassium. As the acetate, sodium acetate and potassium acetate are preferred, and potassium acetate is particularly preferred.

[0125] [Vinyl acetate production catalyst]

[0126] The mass of the metallic copper carried by each 1 kg of the carrier is preferably 0.25 g or more, more preferably 0.60 g or more, and further preferably 0.80 g or more. The mass of the metallic copper carried by each 1 kg of the carrier is preferably 5.00 g or less, more preferably 4.50 g or less, and further preferably 4.00 g or less. These upper and lower limits may be combined arbitrarily. The mass of the metallic copper carried by each 1 kg of the carrier is preferably 0.25 g to 5.00 g, more preferably 0.60 g to 4.50 g, and further preferably 0.80 g to 4.00 g.

[0127] The mass of the metal palladium supported by each 1kg carrier is preferably 5.00g or more, more preferably 8.00g or more, and further preferably 10.0g or more. The mass of the metal palladium supported by each 1kg carrier is preferably 20.0g or less, more preferably 19.0g or less, and further preferably 17.0g or less. These upper and lower limits can be combined arbitrarily. The mass of the metal palladium supported by each 1kg carrier is preferably 5.00g to 20.0g, more preferably 8.00g to 19.0g, and further preferably 10.0g to 17.0g.

[0128] The mass of the metal gold carried by each 1kg carrier is preferably 4.00g or more, more preferably 6.00g or more, and further preferably 8.00g or more. The mass of the metal gold carried by each 1kg carrier is preferably 20.0g or less, more preferably 18.0g or less, and further preferably 17.0g or less. These upper and lower limits can be combined arbitrarily. The mass of the metal gold carried by each 1kg carrier is preferably 4.00g to 20.0g, more preferably 6.00g to 18.0g, and further preferably 8.00g to 17.0g.

[0129] The mass of acetate supported per kg of the carrier is preferably 40 g or more, more preferably 50 g or more. The mass of acetate supported per kg of the carrier is preferably 125 g or less, more preferably 88 g or less. These upper and lower limits may be combined arbitrarily. The mass of acetate supported per kg of the carrier is preferably 40 g to 125 g, more preferably 50 g to 88 g.

[0130] In one embodiment, the catalyst for the production of vinyl acetate obtained by the method of the present disclosure has an eggshell structure in which most of copper, palladium and gold are loaded on the surface portion of the carrier. The thickness of the shell portion varies depending on the type of carrier, alkaline solution and solution containing raw metal compounds used. In the case of using spherical silica with a diameter of 5 mm as a carrier, the shell portion preferably has a thickness of 0.05 to 0.5 mm, and more preferably has a thickness of 0.1 to 0.3 mm. If the thickness of the shell portion is 0.05 mm or more, the catalytic activity can be maintained even if the surface portion of the carrier is peeled off during the reaction. If the thickness of the shell portion is 0.5 mm or less, the catalyst concentration on the surface portion of the carrier can be fully increased, and the advantages of shell-type loading can be economically enjoyed. Acetate does not have to be loaded in a shell form, but can also be uniformly present in the catalyst as a whole.

[0131] [Specific example of catalyst production]

[0132] A specific example of catalyst production is shown below.

[0133] 1. The carrier is impregnated with an alkaline solution in an amount corresponding to the water absorption amount of the carrier.

[0134] 2. The carrier is immersed in a solution A obtained by fixing the volume of raw metal compounds of copper, palladium and gold in excess relative to the desired loading amount of each catalyst component with pure water to 2 times the mass of the water absorption amount of the carrier for a specified time, thereby contacting and impregnating the solution A to form a catalyst precursor that loads the desired amount of catalyst components.

[0135] 3. Separate the catalyst precursor that has been contact-impregnated from the solution obtained in 2.

[0136] 4. The catalyst precursor obtained in 3 is allowed to stand in water or an aqueous solution with a pH of 7.0 to 11.5.

[0137] 5. The catalyst precursor obtained in 4 is brought into contact with a reducing agent to perform a reduction treatment.

[0138] 6. Wash the reduced carrier with pure water.

[0139] 7. Dry the washed carrier.

[0140] 8. Make the carrier carry a specified amount of acetate.

[0141] 9. Dry the carrier carrying the catalyst component.

[0142] [Manufacture of vinyl acetate]

[0143] Hereinafter, a method for producing vinyl acetate using the catalyst for producing vinyl acetate obtained by the method disclosed herein will be described. The reaction for producing vinyl acetate is preferably carried out in a gas phase using acetic acid (HOAc), ethylene and oxygen as reaction raw materials. The gas phase reaction may be in any conventionally known form, but is preferably a fixed bed circulation reaction.

[0144] The reaction formula is shown below.

[0145] CH2=CH2+CH3COOH+1 / 2O2→CH2=CHOCOCH3+H2O

[0146] The ratio of acetic acid, ethylene and oxygen in the raw material gas is preferably acetic acid:ethylene:oxygen=1:0.08-16:0.01-4, more preferably acetic acid:ethylene:oxygen=1:0.2-9:0.07-2 in terms of molar ratio.

[0147] The raw material gas includes ethylene, acetic acid (gas) and oxygen, and may further include nitrogen, carbon dioxide or a rare gas as a diluent as required. When ethylene, acetic acid and oxygen are defined as reaction raw materials, the ratio of reaction raw materials to diluent is calculated as a molar ratio, preferably reaction raw materials: diluent = 1: 0.05 to 9, more preferably reaction raw materials: diluent = 1: 0.1 to 3.

[0148] When the reaction is carried out by a fixed bed flow reaction, the raw material gas is preferably heated at a rate of 10 to 15000 hr under standard conditions. -1 The space velocity (SV) is supplied to the reactor, preferably 300 to 8000 hr -1 The space velocity was set to 10 hr -1 On the other hand, by setting the space velocity to 15000 hr -1 Next, the equipment such as the compressor can be made into a practical size.

[0149] It is preferred to add 0.5 to 20 mol% of water in the form of water vapor, and more preferably 1.0 to 18 mol% of water to the raw gas. Although not limited to any theory, it is believed that the presence of water in the reaction system can suppress the outflow of acetate from the catalyst. Even if more than 20 mol% of water is added, the above effect is not improved, and there is a concern that the hydrolysis of vinyl acetate will progress. Therefore, it is not preferred to allow a large amount of water to exist in the raw gas.

[0150] The material of the reactor is not particularly limited, but a corrosion-resistant material is preferably used.

[0151] The reaction temperature is preferably in the range of 100 to 300° C., more preferably in the range of 120 to 250° C. When the reaction temperature is 100° C. or higher, an appropriate reaction rate can be maintained. When the reaction temperature is 300° C. or lower, it is easy to remove the reaction heat.

[0152] The reaction pressure is preferably in the range of 0 to 3 MPaG (gauge pressure), more preferably in the range of 0.1 to 1.5 MPaG. If the reaction pressure is 0 MPaG or more, an appropriate reaction rate can be maintained. If the reaction pressure is 3 MPaG or less, it becomes unnecessary to make the equipment such as the reaction tube highly pressure-resistant, and the equipment cost can be suppressed.

[0153] As the ethylene used as the reaction raw material, high-purity ethylene is preferably used, but lower saturated hydrocarbons such as methane, ethane, and propane may be mixed therein.

[0154] Oxygen is not particularly limited and can be supplied in the form of oxygen diluted with an inert gas such as nitrogen or carbon dioxide, for example, air. However, when circulating the reaction gas, it is generally advantageous to use high-concentration oxygen, preferably oxygen with a purity of 99% or more.

[0155] Example

[0156] Hereinafter, the present invention will be further described by way of examples, but the present invention is not limited to these examples.

[0157] (Example 1) Preparation of Catalyst A

[0158] A silica sphere carrier (particle diameter 5 mm, specific surface area 155 m 2 / g, water absorption rate 0.85g-water / g-carrier), and prepared into a catalyst by the following steps.

[0159] Step 1. Impregnate 23.5 g of a carrier (water absorption 20.0 g) with an aqueous solution containing 5.3 g of Na2SiO3·9H2O in an amount equivalent to (1.1 times by mass) the water absorption of the carrier. Shake the container containing the carrier and the aqueous solution to completely impregnate the solution, and leave it in a sealed container for 3 hours. The water absorption is calculated from the carrier amount 23.5 g and the water absorption rate 0.85 g-water / g-carrier (the same applies to the following examples and comparative examples).

[0160] Step 2. The carrier obtained in step 1 is immersed in an aqueous solution containing 1.0 g of Na2PdCl4, 0.80 g of HAuCl4 and 0.23 g of copper chloride dihydrate, which is 2 times the mass of the carrier's water absorption amount, and is allowed to stand at room temperature (20°C) for 2 hours to obtain a catalyst precursor on which a desired amount of catalyst components are supported. The standing time is determined by determining the relationship between the amount and time until the catalyst components are supported by a preliminary experiment in advance, and the time to reach the desired supported amount is determined. The desired supported amount of the catalyst components is 13.4 g / kg of palladium, 11.1 g / kg of gold, and 3.3 g / kg of copper per kg of the carrier, and the excess ratio of the input amount of each raw material compound relative to this is set as follows: 16.5% for the compound containing palladium, 77.9% for the compound containing gold, and 10.2% for the compound containing copper.

[0161] Step 3. The catalyst precursor was separated from the solution obtained in step 2 using a metal mesh with a mesh size of 1 mm, and the liquid was drained.

[0162] Step 4. The catalyst precursor obtained in step 3 was immersed in a pH buffer solution (pH = 10.0) containing 0.86 g of NaHCO 3 and 0.68 g of Na 2 CO 3 at 20° C. and 4 times the amount of water absorbed by the support, and allowed to stand at room temperature (20° C.) for 18 hours.

[0163] Step 5. Using the same metal mesh as above, the catalyst precursor was separated from the solution obtained in step 4, and the liquid was drained. The separated catalyst precursor was immersed in an aqueous solution containing 6.1 g of 52% by mass hydrazine hydrate aqueous solution, which was 2 times the water absorption of the carrier, and left to stand at room temperature (20°C) for 4 hours for reduction treatment. Next, the palladium / gold / copper / carrier composition was washed with deionized water, and the washing was continued until chloride ions were no longer present in the washed water. The washed palladium / gold / copper / carrier composition was hot-air dried at 110°C for 4 hours.

[0164] Step 6. At room temperature (20°C), the palladium / gold / copper / carrier composition obtained in step 5 is impregnated with an aqueous solution containing 1.7 g of potassium acetate in an amount equivalent to 0.9 times the weight of the water absorption capacity of the carrier. After standing for 0.5 hours, hot air drying is performed at 110°C for 4 hours to obtain Catalyst A.

[0165] (Example 2) Preparation of Catalyst B

[0166] The desired catalyst component loading amount is changed to 13.5 g / kg of palladium, 10.8 g / kg of gold, and 3.3 g / kg of copper per 1 kg of carrier, and the excess rate of the input amount of each raw material compound relative to this is changed as recorded in Table 1. In step 4 of Example 1, the aqueous solution containing NaHCO3 and Na2CO3 is changed to ion exchange water (pH = 7.0). Except for this, the same operation as Example 1 is carried out to obtain Catalyst B.

[0167] (Comparative Example 1) Preparation of Catalyst C

[0168] A silica sphere carrier (particle diameter 5 mm, specific surface area 155 m 2 / g, water absorption rate 0.85g-water / g-carrier), according to the description of Example 1 of Patent Document 3 (International Publication No. 2022 / 113429), catalyst C was prepared by the following steps.

[0169] Step [1]. Impregnate 23.5 g of a carrier (water absorption: 20.0 g) with an aqueous solution containing 2.3 g of Na2SiO3·9H2O in an amount equivalent to (0.95 times by mass) the water absorption of the carrier. Shake the container containing the carrier and the aqueous solution to completely impregnate the solution, and air-dry for 5 minutes.

[0170] Step [2]. The support obtained in step [1] is immersed in an aqueous solution containing 0.92 g of Na2PdCl4, 0.28 g of HAuCl4 and 0.04 g of cupric chloride dihydrate, which is twice the mass of the support's water absorption capacity, and allowed to stand at room temperature for 20 hours to obtain a catalyst precursor.

[0171] Step [3]. 1.9 g of a 52% by mass aqueous solution of hydrazine hydrate was added to the mixture of the catalyst precursor and the aqueous solution obtained in step [2], and the mixture was gently mixed and allowed to stand at room temperature (20° C.) for 4 hours to perform a reduction treatment. Next, the obtained palladium / gold / copper / support composition was washed with deionized water, and the washing was continued until chloride ions were no longer present in the washed water. The washed palladium / gold / copper / support composition was hot-air dried at 110° C. for 4 hours.

[0172] Step [4]. The palladium / gold / copper / carrier composition is impregnated with an aqueous solution containing 1.7 g of potassium acetate in an amount corresponding to 0.9 times the weight of the water absorption capacity of the carrier at room temperature (20° C.), and hot air drying is performed at 110° C. for 4 hours to obtain a catalyst C. The excess ratio of the input amount of each raw material compound relative to the metal loading amount of the catalyst C determined by the measurement of the metal (copper, palladium and gold) and potassium acetate loading amounts described later is: the compound containing palladium: 5.1%, the compound containing gold: 8.2%, and the compound containing copper: 0%.

[0173] (Comparative Example 2) Preparation of Catalyst D

[0174] A silica sphere carrier (particle diameter 5 mm, specific surface area 155 m 2 / g, water absorption rate 0.85g-water / g-carrier), and according to the description of the example of Patent Document 2 (Japanese Translation of National Publication No. 2002-516749), Catalyst D was prepared by the following steps.

[0175] Step [1]. Impregnate 23.5 g of the carrier (water absorption: 20.0 g) with an aqueous solution containing 0.88 g of Na2PdCl4 and 0.13 g of copper chloride dihydrate in an amount equivalent to the water absorption of the carrier (0.95 times by mass). Shake the container containing the carrier and the aqueous solution to completely impregnate the carrier.

[0176] Step [2]. The support obtained in step [1] is brought into contact with a solution obtained by mixing 0.7 g of a 50 mass % NaOH aqueous solution and 35.7 g of distilled water for 2.5 hours to immobilize palladium and copper on the support in the form of palladium (II) and copper hydroxide.

[0177] Step [3]. The palladium (II) / copper hydroxide / carrier composition obtained in step [2] is washed with deionized water, and the washing is continued until chloride ions are no longer present in the washed water. After washing, the palladium (II) / copper hydroxide / carrier composition is dried for 10 hours at a temperature of 150° C. and nitrogen is circulated. Next, in the gas phase, it is contacted with ethylene (5 mol% in nitrogen) at 150° C. for 5 hours to perform a reduction treatment. The obtained palladium / copper / carrier composition is left to cool for 10 hours, washed with deionized water for 2 hours, and dried in an oven at 150° C. for 5 hours.

[0178] Step [4]. Mix 0.2 g of gold hydroxide and 0.10 g of potassium hydroxide in 17 mL of water, heat the resulting orange suspension to 85°C, and dissolve all solids over 5 hours to obtain a transparent yellow solution of potassium goldate. Add the yellow solution to the palladium / copper / carrier composition obtained in step [3], and impregnate the carrier over 30 minutes. Then, dry the composition in an oven at 100°C under nitrogen flow for 5 hours. Next, use ethylene (5 mol% in nitrogen) to perform a reduction treatment at 120°C for 5 hours to obtain free metallic gold on the carrier.

[0179] Step [5]. The palladium / gold / copper / support composition obtained in step [4] is impregnated with an aqueous solution containing 1.7 g of potassium acetate in an amount corresponding to 0.9 times the weight of the water absorption capacity of the support, and dried at 110° C. for 4 hours to obtain a catalyst D. The excess ratio of the input amount of each raw material compound relative to the metal loading amount of the catalyst D determined by the measurement of the metal (copper, palladium and gold) and potassium acetate loading amounts described later is: compounds containing palladium: 0%, compounds containing gold: 0%, and compounds containing copper: 0%.

[0180] [Evaluation of Catalyst]

[0181] <Determination of metal (copper, palladium and gold) and potassium acetate loading>

[0182] 3 g of the supported catalyst sample was crushed and pressed into a disk with an inner diameter of 3 cm. The metal content of the disk was measured using a fluorescence X-ray spectrometer ZSX Primus II manufactured by Rigaku Co., Ltd. Regarding potassium acetate, the amount of potassium atoms was quantified and converted into potassium acetate.

[0183] 〈Catalytic activity evaluation test〉

[0184] 6.7 mL of the catalyst was diluted with 75 mL of glass beads and filled into a reaction tube (made of SUS316L, inner diameter 22 mm, length 480 mm). Under the conditions of reaction temperature 150°C and reaction pressure 0.6 MPaG, a gas having a gas composition of C2H4 / O2 / H2O / HOAc / N2=45 / 6 / 5 / 23 / 21 (mol%) was circulated at a flow rate of 66.7 NL / h for 240 hours to stabilize the catalyst state. The vinyl acetate activity at a time point of 72 hours from the start of the reaction is recorded in Table 1. Then, the gas flow rate was changed to 20.0 NL / h, and the reaction temperature was further changed to 145°C, 150°C, 155°C or 160°C, and the catalytic activity and selectivity were evaluated. When the gas flow rate and reaction temperature were changed, the catalytic activity and selectivity were evaluated after at least 4 hours had passed and the state of the device and the catalyst was stabilized. Generally, the higher the vinyl acetate activity (STY) (g / L-cat·h), the lower the vinyl acetate selectivity. Therefore, the vinyl acetate selectivity at the same vinyl acetate activity was compared among the catalysts. For example, the vinyl acetate selectivity at a vinyl acetate activity of 800 (g / L-cat·h) was calculated by interpolation from a polynomial approximation curve formed by plotting points of the vinyl acetate activity and the vinyl acetate selectivity at each reaction temperature.

[0185] The reactor outlet gas was analyzed by the following method.

[0186] 1. Oxygen

[0187] By using the absolute standard curve method, 50 mL of the outflow gas was collected and the entire amount was flowed into a 1 mL gas sampler attached to the gas chromatograph, and analysis was performed under the following conditions.

[0188] Gas chromatography: Gas chromatograph (GC-14B manufactured by Shimadzu Corporation) equipped with a Shimadzu gas chromatograph gas sampler (MGS-4: measuring tube 1 mL)

[0189] Column: MS-5A IS 60 / 80 mesh (3mmΦ×3m)

[0190] Carrier gas: Helium (flow rate 20mL / min)

[0191] Temperature conditions: detector temperature and vaporization chamber temperature are 110°C, column temperature is 70°C constant

[0192] Detector: TCD (He pressure 70 kPaG, current 100 mA)

[0193] 2. Acetic acid

[0194] By the internal standard method, 1 mL of 1,4-dioxane was added to 10 mL of the reaction solution as an internal standard, 0.2 μL of which was injected as an analysis solution, and analysis was performed under the following conditions.

[0195] Gas chromatograph: GC-14B manufactured by Shimadzu Corporation

[0196] Column: Packed column Thermon 3000 (length 3m, inner diameter 0.3mm)

[0197] Carrier gas: Nitrogen (flow rate 20mL / min)

[0198] Temperature conditions: detector temperature and vaporization chamber temperature were 180°C, column temperature was maintained at 50°C for 6 minutes from the start of analysis, then increased to 150°C at a rate of 10°C / min, and maintained at 150°C for 10 minutes

[0199] Detector: FID (H2 pressure 40kPaG, air pressure 100kPaG)

[0200] 3. Vinyl acetate

[0201] By the internal standard method, 1 g of 1,4-dioxane was added to 6 g of the reaction solution as an internal standard, 0.3 μL of which was injected as an analysis solution, and analysis was performed under the following conditions.

[0202] Gas chromatograph: GC-9A manufactured by Shimadzu Corporation

[0203] Column: Capillary column TC-WAX (length 30m, inner diameter 0.25mm, film thickness 0.5μm)

[0204] Carrier gas: Nitrogen (flow rate 30mL / min)

[0205] Temperature conditions: detector temperature and vaporization chamber temperature were 200°C, column temperature was maintained at 45°C for 2 minutes from the start of analysis, then increased to 130°C at a rate of 4°C / min, maintained at 130°C for 15 minutes, then increased to 200°C at a rate of 25°C / min, and maintained at 200°C for 10 minutes

[0206] Detector: FID (H2 pressure 60kPaG, air pressure 100kPaG)

[0207] The evaluation results of the catalyst are shown in Table 1. The selectivity of vinyl acetate is based on ethylene.

[0208] Table 1

[0209]

[0210] 1) Catalyst AC is a plant with a vinyl acetate activity (STY) [g / L-cat·h] of 800,

[0211] The vinyl acetate activity of catalyst D is significantly low, so the value at the reaction temperature of 150°C is

[0212] 2) Value at 72 hours from the start of the reaction

[0213] When Example 2 is compared with Comparative Example 1, when compounds respectively containing palladium, gold and copper are reacted with an alkali component while being supported on a carrier, the amount of each metal raw material compound is added in excess relative to the target catalyst component supporting amount, and when the catalyst component supporting amount reaches the target value, the aqueous solution of the metal raw material compound is separated from the carrier, immersed in ion exchange water at pH 7.0, and allowed to stand. As a result, the vinyl acetate selectivity is improved by 0.8 percentage points, and a significant effect is confirmed.

[0214] Industrial Applicability

[0215] According to the present disclosure, a catalyst for producing vinyl acetate having excellent selectivity while ensuring high catalytic activity can be provided. The catalyst for producing vinyl acetate is industrially useful.

Claims

1. A method for producing a catalyst for producing vinyl acetate, which is a method for producing a catalyst for producing vinyl acetate comprising a carrier, copper, palladium, gold and acetate, the method comprising the following steps in order: Step 1. A step of impregnating the carrier with an alkaline solution; Step 2. A step of contacting and impregnating the support with a solution containing copper, palladium and gold as catalyst components and containing a compound containing copper, a compound containing palladium and a compound containing gold in excess amounts relative to a desired amount of each catalyst component supported; Step 3. When the desired amount of each catalyst component is supported by the carrier, a step of separating the carrier from the solution; Step 4. a step of contacting the carrier with water or an aqueous solution having a pH of 7.0 to 11.5; Step 5. A step of performing a reduction treatment; and Step 6. A step of causing the carrier to support acetate. 2 . The production method according to claim 1 , wherein the aqueous solution used in the step 4 is an aqueous solution having a pH of 8.0 to 11.

0. 3 . The production method according to claim 2 , wherein the aqueous solution with a pH of 8.0 to 11.0 is a pH buffer solution.

4. manufacture method according to claim 3, described pH buffer solution is any buffer solution in carbonic acid-bicarbonic acid buffer solution, boric acid (sodium) buffer solution and boric acid (potassium) buffer solution. The method according to claim 3 , wherein the pH buffer solution is a carbonic acid-bicarbonate buffer solution. 6 . The production method according to claim 1 , wherein in the step 2, the excess rate of the input amount of the gold-containing compound relative to the desired gold loading amount is 2% to 150%. 7 . The production method according to claim 1 , wherein in the step 2, the excess rate of the input amount of the palladium-containing compound relative to the desired palladium supported amount is 2% to 50%. 8 . The production method according to claim 1 , wherein in the step 2, the excess rate of the input amount of the copper-containing compound relative to the desired copper loading amount is 2% to 50%. 9 . The production method according to claim 1 , wherein the mass of the metallic copper supported on 1 kg of the carrier is 0.25 g to 5.00 g. 10 . The production method according to claim 1 , wherein the mass of the metal palladium supported on 1 kg of the carrier is 5.00 g to 20.0 g. 11 . The production method according to claim 1 , wherein the mass of the metal gold supported on 1 kg of the carrier is 4.00 g to 20.0 g. 12 . The production method according to claim 1 , wherein the mass of the acetate supported on the carrier per 1 kg is 40 g to 125 g.

13. A method for producing vinyl acetate, the method comprising using as a catalyst a catalyst for producing vinyl acetate obtained by the method according to any one of claims 1 to 5, and using as raw materials ethylene, oxygen and acetic acid.